AWARENESS, PERCEPTION, AND WILLINGNESS TO CONTRIBUTE TO MICRO WAQF BANKS AMONG MUSLIMS IN INDONESIA - Maulana, Agus; Darmastuti, Dewi (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2020)
The purpose of this study is to assess the level of awareness, perception, and willingness that Indonesian Muslims towards waqf and Micro Waqf Banks (MWB). By distributing questionnaires to 104 Muslims, the results show that many Muslims still have a relatively low level of awareness about waqf and MWB. This may be due to the lack of socialization, especially regarding cash waqf and the establishment of MWB. Further findings indicate that the majority of Muslims in Indonesia agree on the establishment of MWB and also agree that MWB can be a solution to suppress the loan shark business so as to improve the welfare of the community, especially the lower middle class. Finally, Indonesian Muslims are willing to contribute to MWB especially if they know how to donate and how MWB operates. A higher level of willingness to contribute to MWB provides a great opportunity for MWB to develop its operations in the future. This research contributes to assisting MWB and Indonesian Waqf Board in developing appropriate socialization strategies to build and develop the potential of waqf in Indonesia.